EFEKTIVITAS DAN KONTRIBUSI PAJAK HOTEL DAN RESTORAN TERHADAP PENDAPATAN ASLI DAERAH KOTA SURAKARTA - bijak saputro, eka arif (KRISNA: Kumpulan Riset Akuntansi, 2020)
Regional Original Income (PAD) is a source of regional finance and government financing. One of the revenues from PAD originating from regional taxes, hotel tax receipts and restaurant taxes, is a potential sector in increasing the effectiveness of hotel and restaurant tax revenues, the contribution given can spur economic development in Surakarta City. The study was conducted at the Surakarta City Financial and Asset Management Revenue Agency. The analytical method used is descriptive quantitative method that is analyzing the target data and the realization of hotel tax receipts and restaurant taxes in 2012-2017 using the effectiveness and contribution ratios. The results of the study indicate that the effectiveness of hotel taxes and restaurant taxes in 2012 - 2017 varies. The highest level of hotel tax effectiveness in 2013, the lowest in 2015, restaurant tax had the highest effectiveness in 2016 and the lowest in 2015. Overall, the contribution of hotel tax and restaurant tax in 2012 - 2017 contributed significantly less to PAD.